Comparative Study of Acceptance Between Local Communities and Transmigrants on The Existence of PT XYZ in Tenggarong Seberang, Kutai Kartanegara - Giwa Giwangkara; Budi Santosa (Journal of Social Research, 2024)
Social License to Operate (SLO) or is a measure that describes the quality of relationships between stakeholders, especially the community and the company. This SLO is the final result or resultant of a series of previous activities including: issue identification, stakeholder identification, stakeholder mapping, stakeholder involvement and implementation of Community Development and Empowerment or PPM programs. This research aims to: 1) what is the pattern of stakeholder engagement carried out by the company, 2) what is the pattern of implementation of the PPM program carried out by the company, 3) what is the comparison of SLO values between local communities and immigrants/transmigrants, 4) what strategy should the company carry out regarding stakeholders engagement refers to the SLO value and 5) how the company contributes to achieving the SDGs. The research location was in four PT XYZ ring 1 villages in Tenggarong Seberang District, Kutai Kartanegara Regency, namely Embalut Village, Separi Village, Bangunrejo Village and Kertabuana Village. The results of the research show that the SLO value of local residents' villages during the operational period was higher than the SLO value of transmigrant villages, namely 3.77 versus 3.46. Meanwhile, during the mine closure period, the SLO value of local villages wasmuch lower than that of trans villages, namely 2.63 compared to 3.19. Referring to these results, the researchers recommend that companies carry out better stakeholder mapping and involvement so that community acceptance, especially local communities, of the company becomes better. This is very important so that when the company wants to do new business other than coal after the mine closure process is accepted by the government it can run smoothly without any significant social risks arising.